Funding and logistical support in The carthagian army from the 5 th century to the era of Hannibal in the 3 rd century B.C. - righi, Mourad (Journal of Social Sciences and Humanities, 2021)
This study aims to know the sources of financing and logistical support in the Carthaginian army, so fighting a war requires providing all the requirements of the army, including food, clothing, transportation, ports and health care. Therefore, Carthage spared did no effort to succeed in its military operations that it was fighting away from its lands from the fifth century to the era of Commander Hannibal in the third century BC. And it is clear that she was keen ancious from the first sight by all means to guarantee the sources of grains, from Sicily, Sardinia and Africa, especially wheat as the first component of the Carthaginian warrior meals, as well instead meat, milk and water, and also provided this warrior with all the items he needed from clothes, and other stuf and provided funds through Imposing taxes, collecting spoils, minting currency, harnessing ports and means of transportation and accompanying peoples in a healthy way. It also provided the role of financing and logistical support was important and decisive in battles and wars, after he believed that the strategic aspect, including armies, plans of conduct of battles, and the competence of leaders, was the one behind the victory of Armies or defeat them.